1997
DOI: 10.1016/s0092-8674(00)80338-4
|View full text |Cite
|
Sign up to set email alerts
|

A Human Endogenous Retroviral Superantigen as Candidate Autoimmune Gene in Type I Diabetes

Abstract: Microbial superantigens (SAGs) have been implicated in the pathogenesis of human autoimmune diseases. Preferential expansion of the Vveta7 T cell receptor positive T cell subset in patients suffering from acute-onset type I diabetes has indicated the presence of a surface membrane-bound SAG. Here, we have isolated a novel mouse mammary tumor virus-related human endogenous retrovirus. We further show that the N-terminal moiety of the envelope gene encodes an MHC class II-dependent SAG. We propose that expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
247
2
8

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(261 citation statements)
references
References 49 publications
(35 reference statements)
4
247
2
8
Order By: Relevance
“…An exogenous type B/D retrovirus (jaagsiekte sheep retrovirus (JSRV)) is the causal agent of SPA [7] and appears to replicate mainly in the transformed epithelial cells [8]. Renewed speculation regarding the involvement of a retrovirus in BAC [9] has been supported by the association of retroviruses, other than human immunodeficiency virus and human T-cell leukaemia virus, with several diseases of humans, such as seminoma [10], undifferentiated germ cell tumours [11], multiple sclerosis [12], acute-onset type I diabetes [13] and Sjo Ègren's syndrome [14]. In order to address this issue, a panel of human lung tumours and relevant nontumour lung lesions were examined immunohistochemically using an antiserum to JSRV capsid protein (JSRV-CA).…”
mentioning
confidence: 99%
“…An exogenous type B/D retrovirus (jaagsiekte sheep retrovirus (JSRV)) is the causal agent of SPA [7] and appears to replicate mainly in the transformed epithelial cells [8]. Renewed speculation regarding the involvement of a retrovirus in BAC [9] has been supported by the association of retroviruses, other than human immunodeficiency virus and human T-cell leukaemia virus, with several diseases of humans, such as seminoma [10], undifferentiated germ cell tumours [11], multiple sclerosis [12], acute-onset type I diabetes [13] and Sjo Ègren's syndrome [14]. In order to address this issue, a panel of human lung tumours and relevant nontumour lung lesions were examined immunohistochemically using an antiserum to JSRV capsid protein (JSRV-CA).…”
mentioning
confidence: 99%
“…The two groups are significantly different (p<0.0001) as determined by the log rank test. Gp70-deficient mice mediate more antigen-specific cytotoxic activity than gp70-sufficient mice in vitro and in vivo 51 Cr-labeled CT26 (A) and peptide-loaded MC57G-Ld (B) cells were combined with increasing numbers of the CT-T cell clone [dashed lines, [30]] or splenocytes from young (less than 4-months old) congenic mice backcrossed 3 generations, then intercrossed: gp70-deficient (diamonds), and gp70-sufficient mice (circles). B.…”
Section: Discussionmentioning
confidence: 99%
“…However, as shown here, these endogenous viruses may also be expressed in normal peripheral tissues. Thus, responses to targeted retroviral TAAs may lead to autoimmunity [51] or antigen-specific T cell tolerance. This range of possible responses to a protein with unknown regulation and with no necessary function to the cell may help to explain the variability in tumor-specific responses in experimental and clinical observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serrez et al showed rapid development of high titer of autoantibodies against type C retrovirus shortly after weaning, approximately at the time that insulitis is initiated [27]. On the other hand, Conrad et al suggested that the endogenous retroviral gene encoding superantigenic activity constituted a candidate autoimmune gene in human IDDM [36], although several groups reported an argument about specificity of endogenous retroviral expression in IDDM patient [37,38,39,40].…”
Section: Discussionmentioning
confidence: 99%